2017
DOI: 10.1177/0278364917710540
|View full text |Cite
|
Sign up to set email alerts
|

A study measuring the impact of shared decision making in a human-robot team

Abstract: This paper presents the results of a user study in which the impact of sharing decision making in a human-robot team was measured. In the experiments outlined here, a human and robot play a game together in which the robot searches an arena for items, with input from the human, and the human-robot team earns points for finding and correctly identifying the items. The user study reported here involved 60 human subjects. Each subject interacted with two different robots. With one robot, the human acted as a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Moreover, participants viewed higher levels of agent autonomy as less burdensome to work with (Johnson et al, 2012) and as requiring a lower workload (Wright et al, 2013, 2018). Finally, humans perceived better collaboration, stronger trust, and increased level of task understanding with greater levels of agent autonomy (e.g., Azhar & Sklar, 2017). A caveat, however, is that other studies by Wright and colleagues found that autonomous agents were better perceived when they provided a moderate level of decision-making input compared to a low or high level (Ruff et al, 2002; Wright & Kaber, 2003, 2005).…”
Section: Results Of Literature Review: Research Environments Themes A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, participants viewed higher levels of agent autonomy as less burdensome to work with (Johnson et al, 2012) and as requiring a lower workload (Wright et al, 2013, 2018). Finally, humans perceived better collaboration, stronger trust, and increased level of task understanding with greater levels of agent autonomy (e.g., Azhar & Sklar, 2017). A caveat, however, is that other studies by Wright and colleagues found that autonomous agents were better perceived when they provided a moderate level of decision-making input compared to a low or high level (Ruff et al, 2002; Wright & Kaber, 2003, 2005).…”
Section: Results Of Literature Review: Research Environments Themes A...mentioning
confidence: 99%
“…We also note that it may not be surprising that increases in agent autonomy had favorable results, given that 11 of the 15 papers manipulated agent autonomy based on the amount of tasks that the autonomous agent could perform. This can be contrasted with the autonomous agent providing high levels of information exchange and decision support (e.g., Azhar & Sklar, 2017). Table 3 contains additional future research opportunities.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, knowledge is based on subjective interpretation (Dodd et al, 2005;Sanzogni et al, 2017), and exists in people and their practices, networks, interactions, and epistemic cultures. Thus, humans and robots can form interactive collaborative teams (Azhar & Sklar, 2017). Information is exchanged from human to robot and from robot to human as indicated in "dynamic interaction" in human-nonhuman collaborative teams (Goodrich & Schultz, 2008, pp.…”
Section: Robots: From Passive Agents To Active Actors In Knowledge-cr...mentioning
confidence: 99%
“…The major challenge here is generating the kinds of explanation and probing dialogue that human users will require from the system. From previous work [10], we know that providing argumentation-based explanations can improve the solutions found by some kinds of human-machine team. The question is whether the kinds of arguments that we can construct to explain plans are considered adequate.…”
Section: Argumentationmentioning
confidence: 99%